Mean arterial pressure estimated by brachial pulse wave analysis and comparison with currently used algorithms. Issue 11 (November 2020) - Grillo, Andrea; Salvi, Paolo; Furlanis, Giulia; Baldi, Corrado; Rovina, Matteo; Salvi, Lucia; Faini, Andrea; Bilo, Grzegorz; Fabris, Bruno; Carretta, Renzo; Benetos, Athanase; Parati, Gianfranco
Abstract : Objective: Mean arterial pressure (MAP) is usually calculated by adding one-third of pulse pressure (PP) to DBP. This formula assumes that the average value of pulse waveform is constant in all individuals and coincides with 33.3% of PP amplitude (MAP = DBP + PP × 0.333). Other formulas were lately proposed to improve the MAP estimation, adding to DBP an established percentage of PP: MAP = DBP + PP × 0.40; MAP = DBP + PP × 0.412; MAP = DBP + PP × 0.333 + 5 mmHg. Methods: The current study evaluated the integral of brachial pulse waveform recorded by applanation tonometry in 1526 patients belonging to three distinct cohorts: normotensive or hypertensive elderly, hypertensive adults, and normotensive adults. Results: The percentage of PP to be added to DBP to obtain MAP was extremely variable among individuals, ranging from 23 to 58% (mean: 42.2 ± 5.5%), higher in women (42.9 ± 5.6%) than men (41.2 ± 5.1%, P  < 0.001), lower in the elderly cohort (40.9 ± 5.3%) than in the general population cohort (42.8 ± 6.0%, P  < 0.001) and in the hypertensive patients (42.4 ± 4.8%, P  < 0.001). This percentage was significantly associated with DBP (β = 0.357, P  < 0.001) and sex (β = 0.203, P  < 0.001) and significantly increased after mental stress test in 19 healthy volunteers (from 39.9 ± 3.2 at baseline, to 43.0 ± 4.0, P  < 0.0001). The average difference between MAP values estimated by formulas, compared with MAP assessed on the brachial tonometric curve, was (mean ± 1.96 × SD): −5.0 ± 6.7 mmHg when MAP = DBP + PP × 0333; −1.2 ± 6.1 mmHg when MAP = DBP + PP × 0.40; −0.6 ± 6.1 mmHg when MAP = DBP + PP × 0.412; −0.4 ± 6.7 mmHg when MAP = DBP + PP × 0.333 + 5. Conclusion: Due to high interindividual and intraindividual variability of pulse waveform, the estimation of MAP based on fixed formulas derived from SBP and DBP is unreliable. Conversely, a more accurate estimation of MAP should be based on the pulse waveform analysis.